Multi-Institutional Registry for Prostate Cancer Radiosurgery: A Prospective Observational Clinical Trial - Freeman, Debra; Dickerson, Gregg; Perman, Mark (Frontiers in Oncology, 2015)
Title: Multi-institutional Registry for Prostate Cancer Radiosurgery: An Observational Clinical Trial Authors: Debra Freeman, MD*; Gregg Dickerson, MD; Mark Perman, MD Objective: To report on the design, methodology and early outcome results of a multi-institutional registry study of prostate cancer radiosurgery. Methods: The Registry for Prostate Cancer Radiosurgery (RPCR) was established in 2010 to further evaluate the efficacy and toxicity of prostate radiosurgery (SBRT) for the treatment of clinically localized prostate cancer. Men with prostate cancer were asked to voluntarily participate in the Registry. Demographic, baseline medical and treatment-related data were collected and stored electronically in a HIPAA-compliant database, maintained by Advertek, Inc. Enrolled men were asked to complete short, multiple choice questionnaires regarding their bowel, bladder and sexual function. Patient-reported outcome forms were collected at baseline and at regular intervals (every 3-6 months) following treatment. Serial PSA measurements were obtained at each visit and included in the collected data. Results: From July 2010 to July 2013, nearly 2000 men from 45 participating sites were enrolled in the registry. The majority (86%) received radiosurgery as monotherapy. At 2 years follow-up, biochemical disease free survival was 92%. No Grade 3 late urinary toxicity was reported. One patient developed Grade 3 gastrointestinal toxicity (rectal bleeding). Erectile function was preserved in 80% of men <70 yeats old. Overall compliance with data entry was 64%. Conclusion: Stereotactic radiosurgery is an alternative option to conventional radiotherapy for the treatment of organ-confined prostate cancer. The Registry for Prostate Cancer Radiosurgery represents the collective experience of multiple institutions, including community-based cancer centers, with outcome results in keeping with published, prospective trials of prostate SBRT.